Inter-vendor variance of enteric eukaryotic DNA viruses in specific pathogen free C57BL/6N mice. (May 2021) - Rasmussen, Torben Sølbeck; Jakobsen, Rasmus Riemer; Castro-Mejía, Josué L.; Kot, Witold; Thomsen, Allan Randrup; Vogensen, Finn Kvist; Nielsen, Dennis Sandris; Hansen, Axel Kornerup
Abstract: The laboratory mouse strain C57BL/6 is widely used as an animal model for various applications. It is becoming increasingly clear that the bacterial enteric community highly influences the phenotype. Eukaryotic viruses represent a sparsely investigated member of the enteric microbiome that might also affect the phenotype. We here investigated the presence of enteric eukaryotic DNA viruses (EDVs) in specific pathogen-free (SPF) C57BL/6N mice purchased from three vendors upon arrival and after being fed a low-fat diet (LFD) or high-fat diet (HFD). We detected genetic fragments of EDVs belonging to the viral families of Herpes -, Mimi-, Baculo- and Phycodnaviridae represented by two genera; Chlorovirus and Prasinovirus . The EDVs were detected in the mice upon arrival and persisted for 13 weeks. However, these signals of EDVs were only detected at notable levels in mice fed LFD from 2 out of 3 vendors, which suggested that the enteric composition of these EDVs were affected by both vendor ( p  < 0.003) and different dietary regimes ( p  < 0.013). This highlights the need of additional studies assessing the potential function of these EDVs that may influence the mouse phenotype and the reproducibility of animal studies using this C57BL/6N substrain. Highlights: Enteric eukaryotic DNA viruses were detected in the intestinal content from specific pathogen-free C57BL/6N mice. Known and unknown features associated to Herpes -, Mimi-, Baculo-, and Phycodnaviridae may affect the mouse phenotype. Inter-vendor variance was observed in the composition of the enteric eukaryotic DNA viruses.